Impact of age, sex and ethnicity on intra-cardiac flow components and left ventricular kinetic energy derived from 4D flow CMR. (1st August 2021) - Zhao, Xiaodan; Tan, Ru-San; Garg, Pankaj; Chai, Ping; Leng, Shuang; Bryant, Jennifer; Teo, Lynette L.S.; Ong, Ching Ching; Geest, Rob J. van der; Allen, John C.; Yip, James W.; Tan, Ju Le; et al.
Abstract: Background: Four-dimensional flow cardiovascular magnetic resonance (4D flow CMR) allows quantification of left ventricular (LV) blood flow. We aimed to 1) establish reference ranges for 4D flow CMR-derived LV relative flow components and kinetic energy parameters indexed to end-diastolic volume (KEiEDV ) among healthy Asian subjects, 2) assess effects of age and sex on these parameters, and 3) compare these parameters between Asian and Caucasian subjects. Methods: 74 healthy Asian subjects underwent cine and 4D flow CMR. Relative flow components (direct flow, retained inflow, delayed ejection flow, residual volume) and multiple phasic KEiEDV (LV global, peak systolic, systolic, diastolic, peak E -wave, peak A-wave) were analyzed. Sex- and age-specific reference ranges were reported. Results: Relative flow components and systolic phase KEiEDV did not vary with age. Women had higher retained inflow and peak E -wave KEiEDV, lower residual volume, peak systolic and systolic KEiEDV than men. Peak A-wave KEiEDV increased significantly ( r = 0.474) whereas peak E -wave KEiEDV ( r = −0.458) and E-wave/A-wave ratio ( r = −0.528) decreased with age. A sub-population ( n = 44) was compared with 44 sex- and age-matched Caucasian subjects: no significant group differences were observed for all 4D flow CMR parameters. Conclusion: Asian sex- and age-specific 4D flow CMR reference ranges were established. Sex differences in retained inflow, residual volume, peak systolic, systolic KEiEDV and peak E -wave KEiEDV were observed. Ageing influenced diastolic KEiEDV but not systolic phase KEiEDV or relative flow components. All studied parameters were similar between sex- and age-matched Asian and Caucasian subjects, implying generalizability of the ranges. Highlights: Sex- and age-specific 4D flow CMR reference ranges of LV flow components and KE were established in a largest Asian cohort. Ageing influenced diastolic KEiEDV but not systolic phase KEiEDV or relative flow components. Women had higher retained inflow and peak E -wave KEiEDV, lower residual volume, peak systolic and systolic KEiEDV than men. All 4D flow parameters had similar values for sex- and age-matched Asian and Caucasian, implying ranges' generalizability.